Experimental Investigation of Flame Spread Characteristics in Cable Fires Within Covered Trays Under Different Tilt Angles - Changkun Chen; Yipeng Bao; Boyuan Zuo; Jia Zhang; Yuhuai Wang (Fire)
In the actual installation of cables, inclined cable laying within covered cable trays is a relatively common method. To investigate the effects of different tilt angles on the combustion behavior of cables within covered cable trays, aluminum conductor polyethylene-insulated power cables were used as the test cables. The flame morphology, temperature distribution, and fire spread rate during the cable combustion process were analyzed for experimental scenarios for which the cable laying angles and the ignition positions changed. The results indicate that the inclination angle of the covered cable tray has a significant impact on flame propagation and temperature distribution. For the ignition located at the lowest part of the cable, the fire spread rate increases significantly with the tilt angle. In contrast, for the ignition located at the highest part of the cable, the fire spread rate initially decreases slightly and then increases, with a relatively smaller overall change in magnitude. Under both ignition positions, the flame spread rate significantly increases at 15–30°. Therefore, in actual cable installation processes, cables within covered troughs should avoid large-angle inclinations.